The Olfactory Dysfunction of COVID-19 - Doty, Richard L. (Seminars in Neurology, 2023)
Until the coronavirus disease 2019 (COVID-19) pandemic, much of the scientific community and the general public lacked an appreciation of the impact of decreased smell function on everyday life, including the importance of this sensory system for safety, nutrition, and overall quality of life. It is now well established that the SARS-CoV-2 virus inflicts measurable but frequently reversible smell loss during its acute phase. Indeed, in many studies such loss is the most common symptom of COVID-19. Permanent or long-term deficits (i.e., deficits lasting over a year) may occur in up to 30% of those who have been infected, including the development of odor distortions (dysosmias; parosmias). This review presents up-to-date information on the epidemiology, severity, and pathophysiology of COVID-19-related smell dysfunction, including its association with psychological and neurological sequelae.
Keywords: COVID-19; olfaction; anosmia; SARS-CoV-2; taste